PENGARUH TEKNIK MEMBACA SQ3R TERHADAP MEMBACA PEMAHAMAN MAHASISWA FKIP UNIVERSITAS BUNG HATTA PADANG - Gusnetti Gusnetti; M. Zaim; Syahrul Ramadhan; Agustina Agustina (Ta'dib, 2018)
The main issue discussed in this article is the students’ low interest in reading textbooks. In addition, students do not use various techniques. As a result, they feel bored, and less concentrated when reading. The theory used in this research is the reading theory proposed by Tarigan (2008), reading comprehension techniques by Agustina (2008) and SQ3R reading techniques by Ermanto (2008) and Agustina (2008). This type of research is quantitative research using experimental method with SQ3R reading techniques. The population of this study were Indonesian Language and Literature Education students of FKIP Bung Hatta University who took the Reading Teaching Skills course. The sample was elected purposively. Based on data analysis, it was found that students did not apply the SQ3R reading technique well in determining the theme, plot, background, characterization, point of view and mandate, with an average value of 80.5. Thus, it can be concluded that there is a significant effect of the use of SQ3R reading techniques towards students’ reading comprehension at FKIP of Bung Hatta University Padang.